Manajemen Pengetahuan Dosen dalam Pembelajaran Bahasa Arab di Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga Yogyakarta - Laelatul Badriyah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2015)
students who have deep thesis writing skills Arabic and the ability of students who have the ability of the Arabic language comprehensively is still small. this becomes a homework great for PBA majors. Knowledge management as one alternative to reduce the ability gap of students can implemented by doing good cooperation between facilitator (lecturer) and student to share knowledge in class. Results research shows that lecturer knowledge management in the department PBA has occurred even though it still has to make improvements to combination process. As for the implementation of deep knowledge management Arabic learning has not taken place maximally due to lack of awareness to share knowledge between students.